Human mucosal CD4+ T cells but not blood CD4+ T cells respond vigorously towards CD28 engagement - Schröder-Braunstein, Jutta; Pavlov, Vladimir; Giese, Thomas; Heidtmann, Antje; Wentrup, Sabine; Lasitschka, Felix; Ulrich, Alexis; Engelke, Antonia; Saeedi, Mohammed al; Meuer, Stefan (Clinical & experimental immunology, 2012)
Human lamina propria T lymphocytes (LPT) possess functional properties profoundly different from those of peripheral blood T lymphocytes (PBT). While they are characterized by a low proliferative response to T cell receptor (TCR)/CD3 stimulation in vitro their responsiveness to activation through the ‘co-stimulatory’ CD2-receptor is enhanced when compared to PBT. In this study, we demonstrate that engagement of another co-stimulatory receptor on both LPT and PBT, namely CD28, by a single monoclonal antibody (mAb), respectively, strongly activates the former but not the latter through a PI3-kinase dependent signalling pathway leading to the production of inflammatory cytokines such as interleukin (IL)-2, tumour necrosis factor (TNF)-α, interferon (IFN)-γ and granulocyte-macrophage colony-stimulating factor (GM-CSF). In addition to the high sensitivity of LPT to CD2 stimulation, this finding supports the notion that ‘non-specific/innate’ mechanisms to activate T lymphocytes play a predominant role vis-à-vis‘TCR driven/adaptive’ responses in the intestinal mucosa. Furthermore, it suggests that results from preclinical tests for therapeutic antibodies performed with human blood derived T cells are probably insufficient to predict reactivities of tissue-resident immune cells, which - given their quantitative predominance - may critically determine the in-vivo response to such compounds.
Published online: 28 November 2011
Gesehen am 11.04.2018